Ontology of Technology (International Journal of Scientific Trends, 2026)
This article provides a scientific and philosophical analysis of the essence of technology and its social significance. It examines the scientific interaction of technology with such social spheres as labor, activity, science, and culture. From a scientific and philosophical standpoint, the role and significance of theoretical knowledge in production processes are explored, along with the concept of the human factor.